People's Economy Education as an Instrument for Achieving the SDGs: A Study of SDG 8, SDG 10, and SDG 12 - Gumanti, Dessyta; Baroroh, Kiromim; Astuti, Widya (Indo-MathEdu Intellectuals Journal, 2026)
The global economy is currently facing major problems such as social inequality, environmental damage, and lack of access to economic education for the people. Economic education for the people is an important way to achieve inclusive sustainable development in this regard. This article aims to examine how economic education for the people helps achieve the three Sustainable Development Goals (SDGs). SDG 8 relates to economic education for the people, decent work, and economic growth; SDG 10 relates to reducing inequality; and SDG 12 relates to responsible consumption and production. According to this study, economic education for the people has the potential to shape economic behavior that is oriented towards sustainability, cooperation, and independence. This is based on a literature review conducted by various national and international sources. Since micro, small, and medium enterprises (MSMEs) in Indonesia employ around 97% of the workforce and contribute more than 61% of GDP, there is ample evidence that the people's economic base plays a strategic role in supporting SDG 8. Economic education that emphasizes economic democracy, equal access, and social solidarity also helps reduce inequality (SDG 10) and encourages more sustainable production and consumption practices. This article also emphasizes that the people's economy must be further integrated into formal and non-formal education systems as a long-term policy strategy. Therefore, people's economy education is beneficial for both national development and fair, inclusive, and sustainable global development plans